2019
DOI: 10.1111/bjd.17596
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations in mevalonate kinase cause disseminated superficial actinic porokeratosis

Abstract: Summary Background Disseminated superficial actinic porokeratosis (DSAP) is a rare autosomal dominant disease. In our previous research, we found that a linkage region of DSAP in a large family is located at 12q23·2-q24·1. Subsequently, the mevalonate kinase gene (MVK) was shown to be pathogenic in DSAP. Objectives To elucidate the mechanism by which MVK mutations lead to keratinocyte apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
0
14
2
Order By: Relevance
“…In this randomized clinical trial, we compared the efficacy and safety of topical lovastatin-cholesterol cream vs topical lovastatin cream in participants with DSAP. The addition of topical cholesterol is speculated to offset lovastatin’s influence on cholesterol downregulation . Although prior studies have suggested more favorable effects with the combination drug, results were nonsignificant, and our results showed no significant difference between the treatment groups, suggesting that the addition of cholesterol during the first 3 months of treatment was ineffective.…”
Section: Discussioncontrasting
confidence: 80%
“…In this randomized clinical trial, we compared the efficacy and safety of topical lovastatin-cholesterol cream vs topical lovastatin cream in participants with DSAP. The addition of topical cholesterol is speculated to offset lovastatin’s influence on cholesterol downregulation . Although prior studies have suggested more favorable effects with the combination drug, results were nonsignificant, and our results showed no significant difference between the treatment groups, suggesting that the addition of cholesterol during the first 3 months of treatment was ineffective.…”
Section: Discussioncontrasting
confidence: 80%
“…MVK is best known for its role in mevalonate kinase deficiency (44), although this is linked to the decreased production of isoprenoids in a branch pathway (Figure 1), rather than the production of cholesterol. Some pathogenic mutations in MVK cause rapid proteasomal degradation of the enzyme (45). MVK has also been identified as the Luteinizing hormone receptor (LHR) mRNA binding protein (LRBP), for which its role is regulated by SUMOylation, with no known consequence for cholesterol synthesis (46).…”
Section: Early Pathway Enzymesmentioning
confidence: 99%
“…Since then, several other DSAP patients with different germline MVK mutations have been reported. 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 In 2015, and confirmed later, heterozygous germline mutations in genes encoding three other enzymes downstream of MK in the mevalonate pathway (i.e., mevalonate diphosphodecarboxylase [ MVD ], phosphomevalonate kinase, and farnesyl diphosphate synthase) were also found to cause DSAP and other PK subtypes ( Fig. 2 ).…”
Section: The Clinical and Genetic Landscape Of Mk-associated Diseasesmentioning
confidence: 70%
“…Zhu et al. 55 recently demonstrated decreased kinase activity, reduced cholesterol production, and increased apoptosis in cells transfected with two MVK pathogenic variants identified in DSAP patients. Shortage of isoprenoids could predispose patients to idiopathic inflammation of the skin because the mevalonate pathway is crucial in regulating calcium-induced keratinocyte differentiation and proliferation.…”
Section: The Clinical and Genetic Landscape Of Mk-associated Diseasesmentioning
confidence: 99%